MODERN APPROACHES TO ORGANIZING INDEPENDENT EDUCATION OF STUDENTS - Muminova Nargiza Abdurakhmanovna (Bright Mind Publishing, 2025)
In the rapidly evolving educational landscape, independent education plays a crucial role in fostering student autonomy, critical thinking, and lifelong learning skills. This article explores modern approaches to organizing independent education, drawing on contemporary theories and practices that enhance learning outcomes. It discusses key strategies, including the integration of digital tools, personalized learning paths, and collaborative environments, that support students in becoming self-directed learners. The practical applications and methods outlined in this article aim to provide educators with insights into effectively implementing independent learning frameworks in diverse educational settings.
Keywords: Independent education, self-directed learning, digital tools, personalized learning, collaborative learning, lifelong learning.